2010
DOI: 10.1177/1091142110376518
|View full text |Cite
|
Sign up to set email alerts
|

What Goes Around Comes Around? Experimental Evidence of the Effect of Rewards on Tax Compliance

Abstract: The current experimental study examined the effect of monetary rewards on tax compliance. Eighty-six participants were randomly assigned to one control and two reward conditions (low vs. high reward). Overall, tax compliance was not affected by the rewards. However, a change in compliance strategies was observed. It seems that rewards provoked an all-or-nothing behavior. Whereas in the reward conditions, participants were either completely honest or evaded all of their income, in the control condition, the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 18 publications
1
42
0
5
Order By: Relevance
“…Alm et al (2012b), argumentam que outros fatores envolvem a decisão do contribuinte, e não somente a maximização do retorno econômico, demonstrando a limitação do paradigma econômico clássico, ao constatar que a probabilidade de ser auditado é mínima. Por esta via (KASTLUNGER et al, 2011), partem de uma abordagem multidisciplinar em seus estudos e acrescentam o direito, a política, a sociologia e a psicologia social.…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation
“…Alm et al (2012b), argumentam que outros fatores envolvem a decisão do contribuinte, e não somente a maximização do retorno econômico, demonstrando a limitação do paradigma econômico clássico, ao constatar que a probabilidade de ser auditado é mínima. Por esta via (KASTLUNGER et al, 2011), partem de uma abordagem multidisciplinar em seus estudos e acrescentam o direito, a política, a sociologia e a psicologia social.…”
Section: Revisão Da Literaturaunclassified
“…Considerando que os contribuintes apresentam comportamentos diferentes perante as suas obrigações fiscais (KASTLUNGER et al, 2011), é possível conjeturar que a percepção que o agente fiscal possa ter com relação ao comportamento do contribuinte no que se refere à justificação ética para a evasão fiscal, pode ser um ponto de partida para entender este fenômeno e suas variantes, uma vez que, nessa relação mais próxima, emergem particularidades motivadas pelas condutas e componente éticos de ambos os atores, que, acreditamos, precisam ser conhecidas. A importância do presente estudo reside no caráter inovador e pioneirismo em avaliar a ética fiscal do contribuinte na perspectiva do agente fiscal com a realização de um inquérito.…”
Section: Metodologiaunclassified
“…filing taxes) than those who thought the opportunity was available to everyone. Kastlunger et al (2011), in an RCT carried out in Italy, investigated the effect of rewards on tax compliance and found that overall there was no effect. In fact, it appears that it provoked an all or nothing type of behaviour for taxpayers.…”
Section: Key Findingsmentioning
confidence: 99%
“…We are aware of only a few laboratory studies of tax compliance mechanisms incorporating rewards: Alm et al (1992a), Bazart and Pickhardt (2011), Kastlunger et al (2011) and Fochmann and Kroll (2014). These designs essentially offer an additional, exogenous, incentive to comply and, perhaps unsurprisingly, find that compliance rates increase.…”
Section: Introductionmentioning
confidence: 99%